STUDY ON INCLUSION OF PROBIOTIC, PREBIOTIC AND ITS COMBINATION IN BROILER DIET AND THEIR EFFECT ON GROWTH PERFORMANCE OF COMMERCIAL BROILERS - Saiyad, MA; Joshi, RS; Savaliya, FP; Patel, AB; Mishra, RK; Bhagora, NJ (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Day-old commercial broiler chicks (n = 200) were distributed randomly into 5 dietary treatment groups, viz. control (T1), probiotic in the feed @ 100 g/tonne (T2), prebiotic in the feed @ 500 g/ tonne of feed (T3), synbiotic (probiotic + prebiotic) @ 100 g/tonne and 500 g/tonne of feed, respectively (T4) and synbiotic (probiotic + prebiotic) @ 50 g/tonne and 250 g/tonne of feed (T5) respectively, and up to 6 weeks of age their performance was evaluated weekly. Results revealed that various feed additives used in the study affected the growth and feed efficiency of chicks significantly (P < 0.05). Body weight at the end of starter phase and whole experiment showed that all treatment groups gained significantly (P<0.05) higher body weight than control group. Highest body weight at the end of starter phase was observed in T5 whereas at the end of experiment T3 recorded highest body weight. The broilers consumed significantly (P<0.05) less amount of feed under synbiotic groups than all others. The FCR was better for the broilers under synbiotic supplemented group (T4) and it was significantly (P<0.05) better than all supplemental groups during finisher phase and during overall study.